Challenges associated with the implementation of occupational safety and health management systems in manufacturing industry of Mutare, Zimbabwe - Mandowa, Johanes; Matsa, Mark; Jerie, Steven (Frontiers in Public Health, 2025)
ObjectiveThis study examines challenges of implementing the Occupational Safety and Health Management System (OSHMS) in the manufacturing industry of Mutare, Zimbabwe as well as to develop a framework to circumvent the identified challenges.MethodsUtilizing a descriptive mixed-method design, data was collected through questionnaires, interviews, and observations, alongside secondary sources like company OSH records. Primary and secondary data was analyzed and discussed continuously in a descriptive prose. Chi-square test at 5% significance level was applied to test inferential statistics and the test results were described qualitatively to compliment other data sources.ResultsKey findings identified inadequate resources, lack of leadership and commitment, insufficient employee involvement, and a shortage of qualified OSH practitioners as major obstacles. The study reveals that causes of these challenges are multifactorial, necessitating comprehensive interventions. A lack of a preventive safety culture emerged as a critical underlying factor affecting OSHMSs implementation.ConclusionIn alignment with Article 14 of ILO Convention 155, the research advocates for a national strategy to foster a preventive OSH culture, integrating OSH into all education and training levels. Additionally, it recommends that the Government of Zimbabwe ratify ILO Convention 187 to support the establishment of a national OSH qualifications framework, enhancing OSH management at both national and workplace levels. This study originality is its ability to develop a problem driven framework of interventions ideal for solving OSH implementation challenges and their causal factors in the manufacturing industry of Mutare through experiential learning, coordination, and a collaborative approach. The study is of global significance as it has an impact of providing opportunities for sustainable OSH transformation in the manufacturing industry of Mutare and beyond.